Microfinance Companies on Entrepreneurship Development in Nepal - Panthi, Babu Ram; Chalise, Ambika (Nepalese Journal of Management Research, 2022)
This is survey based article. It is conducted with different microfinances institutions (MFIs) that branches are located in Bharatpur, Chitwan and Gaidakot, Nawalparasi. Respondents are 120 micro-entrepreneurs and 20 employees of the same MFIs are taken as respondents. Data and information are collected through questionnaires and interview. The questionnaires are distributed among the 120 sample micro-entrepreneurs and 20 employees of MFIs. The relationship between MFIs and entrepreneurships are analyzed through the use of chi square test. The article concluded that MFIs play significant role in enhance micro-enterprises operation. The study concluded that there are various barriers impede entrepreneurs’ development. The major challenges involve negligence of government for the entrepreneurship development and lack of finance for the proper development of the enterprises. Poor financial literacy, poor management of market area and the lack of infrastructure development are also the challenges. Other factors that hindered enterprises growth that was cited by entrepreneurs: Interest rates charged are too high, rigid payment period; local market is not well diversified, high competition among the local entrepreneurs, no support from the local municipality. Despite the various problems and challenges, MFIs have a positive impact on the entrepreneurship development in overall study.